2013
DOI: 10.17576/jkukm-2015-25-04
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Mixtures of Asphalt with Palm Oil Shells and Coconut Shells as Additives

Abstract: The finding of other alternative material that has become the concern of various works lies in the fact that the material is to serve as an additive in asphalt mixes to enhance its physical properties. This paper deals with a laboratory study which compares the performance of hot mix asphalt (HMA) (0,5, 10, 15 and 20%) (0, 5, 10, 15 dan 20%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
3
Order By: Relevance
“…Keteguhan campuran asfalt kepada ubah bentuk plastik disahkan berdasarkan ujian rayapan dinamik (Almansob et al 2013). Peralatan ujian adalah sama seperti ujian rayapan statik, tetapi ujian beban berulang-ulang bahagian itu dibuat dengan cara yang berbeza.…”
Section: Ujian Rayapan Dinamikunclassified
See 2 more Smart Citations
“…Keteguhan campuran asfalt kepada ubah bentuk plastik disahkan berdasarkan ujian rayapan dinamik (Almansob et al 2013). Peralatan ujian adalah sama seperti ujian rayapan statik, tetapi ujian beban berulang-ulang bahagian itu dibuat dengan cara yang berbeza.…”
Section: Ujian Rayapan Dinamikunclassified
“…Terdapat beberapa kajian berkenaan dengan turapan asfalt seperti Shelke et al (2014), Almansob et al (2013), dan Maria dan Albuqueque (2014) telah dijalankan terhadap penggantian agregat dengan tempurung kelapa. Tempurung kelapa dikategorikan sebagai sisa pertanian di mana satu jumlah yang besar sisa pertanian yang telah dijual di kebanyakan negara-negara tropika jika tidak dilupuskan dengan betul ia akan membawa impak negatif kepada masalah sosial dan alam sekitar (Ganiron Jr. 2013;Kambli & Mathapati 2014).…”
unclassified
See 1 more Smart Citation
“…Several literature studies and research related to CA and LDPE found that the asphalt mixture characteristics that use these materials still meet the requirements set by Bina Marga (2014) and AAPA (2004) [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…CF has outstanding moisture absorption because the irregular of crack in the cross section surface made it has unique structure [8]. The unique structure also make it has good air permeability, moisture conductivity, susceptibility, viscoelasticity and rutting resistance as well as meliorate low temperature anti-cracking properties, durability, material toughness, fatigue life and lowering reflective cracking of asphalt concrete mixtures and pavements [4,[9][10][11][12]].…”
Section: Introductionmentioning
confidence: 99%